Design and fabrication of mechanical sand purifier / Ahmad Aiman Suhaimi and Muhamad Faris Syafiq Khalid - Suhaimi, Ahmad Aiman; Khalid, Muhamad Faris Syafiq (School of Mechanical Engineering, 2023)
Sand purification is an essential process in construction and infrastructure development. However, the traditional sand purifier requires two workers to filter and pack the sand, making it time-consuming and costly. This project aims to design and develop a simple sand purifier that will help workers do their job faster while reducing the cost of the sand purifier. The traditional sand purifier requires two workers to filter and pack the sand, making it time-consuming and costly. Most sand purifiers in recent years are also quite expensive, especially automated machines. This limits accessibility for small-scale construction businesses and communities. The primary objective of this project is to design and develop a sand purifier that will filter all the unwanted substances in the sand and pack it into a sandbag with only one worker required. The machine is equipped with mechanical parts and runs using an electric motor, making it more affordable and accessible. The sand purifier was designed and fabricated using mechanical parts and an electric motor to shake the filter. The machine was tested and evaluated for its filtration efficiency, durability, and user-friendliness. The sand purifier developed in this project filtered all the unwanted substances in the sand and packed it into a sandbag with only one worker required, making the job faster and more efficient. The use of mechanical parts and an electric motor reduced the cost of the sand purifier, making it more affordable and accessible to small-scale construction businesses and communities